Continuing early mTICI 2b recanalization may improve functional outcome but is associated with a higher risk of intracranial hemorrhage - Steffen, Paul; Van Horn, Noel; McDonough, Rosalie; Deb-Chatterji, Milani; Alegiani, Anna Christina; Thomalla, Götz; Fiehler, Jens; Flottmann, Fabian (Frontiers in Neurology, 2022)
Background: Successful reperfusion (mTICI 2c/3) and low number of passes are key determinants for good clinical outcome in acute large vessel occlusion. While final mTI-CI 2c/3 reperfusion is superior to partial reperfusion (mTICI 2b) it remains unclear if this is also true for the subgroup of patients with early mTICI 2b (achieved in ≤2 retrieval attempts) reperfusion who are secondarily improved to mTICI 2c/3. This study was de-signed to examine if early mTICI2b should be continued or stopped during mechanical thrombectomy (MT). Methods: 913 ischemic stroke patients who received MT were retrospectively analyzed. Angiography runs following each recanalization attempt were scored for mTICI. The patients with early mTICI 2b reperfusions were dichotomized in “TICI2b-stopped” (MT withdrawal after mTICI 2b was achieved with first or second retrieval) and “TICI2b-continued” (MT was continued after mTICI 2b was achieved with first or second re-trieval). Functional outcome was obtained after 90 days using the modified Rankin scale (mRS90). Results: Of 362 Patients with a M1-occlusion, 100 patients fulfilled the inclusion criteria with an early mTICI 2b. 78/100 patients were included in the “TICI2b-stopped” group and 22/100 patients were in the “TICI2b-continued” group. Of these 22 patients, none had a final mTICI score lower than 2b and 11 patients had a final mTICI score of 2c/3. Regarding good functional outcome at mRS90, “TICI2b-continued” showed by trend a slight advantage of 40.1% vs. 35.6% in “TICI2b-stopped” but in multivariate logistic regression analysis adjusted for confounders, no significant difference was found be-tween the two groups (OR 0.75, 95% CI 0.19-2.87, p=0.67). Symptomatic intracranial hemorrhage was significantly higher in “TICI2b-continued” compared to “TICI2b-stopped” (31.8% vs. 10.3%, p=0.031). Conclusion: Successfully improving an early mTICI 2b to mTICI 2c/3 reperfusion is possible in a substantial number of patients and might improve functional outcome. However, an increase in symptomatic intracranial hemorrhage (SICH) intracranial hem-orrhage due to further retrieval attempts may diminish the potential functional benefit to continue early mTICI 2b. To support this finding, further investigation with more power is needed to account for the low number of events regarding SICH.